Analisis Kepastian Hukum Atas Kepemilikan Tanah Dago Elos terhadap Hak Para Pihak - Frederika Eugenia; Victor Imanuel Williamson Nalle (Universitas Batanghari Jambi, 2025)
Previous studies on agrarian conflict in Indonesia largely emphasized the weak conversion of colonial land rights and the uncertainty of land status but have yet to examine contemporary cases involving document forgery and inconsistent court rulings. The articlee highlights the Dago Elos land dispute as a modern urban agrarian conflict that reflects the fragility of legal certainty. Using an empirical juridical method through analysis of Basic Agrarian Law (UUPA), court decisions, and community interviews, the study finds that expired eigendom verponding claims and forged documents intensified legal insecurity for residents. The findings reveal that land rights protection in Indonesia remains vulnerable, while the state of the art of this research lies in integrating colonial legal legacies, administrative manipulation, and the effectiveness of legal protection in contemporary land disputes.